Toxicological Evaluation of Vanillin Flavor in E-Liquid Aerosols on Endothelial Cell Function: Findings from the Replica Project - R. Emma; A. Sun; K. Partsinevelos; S. Rust; V. Volarevic; R. Lesmana; A. Giordano; H. Goenawan; M. I. Barliana; A. Arsenijevic; N. Kastratovic; V. Markovic; et al. (Cardiovascular Toxicology, 2026)
There are challenges that require collaboration among researchers to ensure that tobacco harm reduction strategies are evidence-based. A key challenge is evaluating the safety of flavors in e-cigarettes. Many flavorings are deemed “generally recognized as safe” (GRAS) for ingestion, but this does not guarantee their safety when inhaled. The Replica international research group is dedicated to the replication of studies on tobacco alternatives. As part of this effort, the group conducted a conceptual replication of the vanillin-specific experiments from the study by Fetterman et al. (2018), with the goal of validating their conclusions regarding this compound. We used Aspire Zelos 3 e-cigarette and prepared e-liquids containing propylene glycol, vegetable glycerin, and vanillin. The e-liquids were vaporized under regular (1 Ohm coil, 14 watts) and sub-Ohm (0.3 Ohm coil, 200 °C) settings using a vaping machine, following ISO20768:2018 puffing regime. The vapor was collected into a trapping solution to prepare aqueous extracts for treating human aortic endothelial cells. We evaluated cytotoxicity, oxidative stress, nitric oxide bioavailability, and inflammation addressing some gaps reported in the original study. We observed some harmful effects mostly attributable to ethanol used to trap vanillin, but no harmful effects from vanillin. Our results confirm the endothelial cell dysfunction observed in the original paper, but clarify that these effects are mainly attributable to ethanol and not to vaporized vanillin, indicating that, under the experimental conditions applied, vanillin does not elicit significant adverse effects on vascular endothelial cells. However, further research is needed to confirm its toxicological profile. Graphical Abstract Created in BioRender. https://BioRender.com/rn8dt1m .

Association between cagemate number and risk of death in mice: a time-varying covariate analysis using Cox frailty models - Thirupathi R. Mokalla; Erik S. Parker; Daniel L. Smith; Luis-Enrique Becerra-Garcia; Olivia C. Robertson; Deependra K. Thapa; Mounika Kandukuri; Bret M. Rust; David B. Allison (GeroScience, 2026)
Social housing is desirable for the health and well-being of laboratory mice, as social interactions with conspecifics influence both behavioral and physiological outcomes. Although group housing benefits social species, it can introduce variability in mortality outcomes, and raise welfare concerns, particularly with the emergence of aggression or fluctuating cage densities. Despite this, few studies have evaluated how changes in the number of living cagemates over time are associated with survival, particularly in a sex-specific manner. We analyzed data from the National Institute on Aging’s Interventions Testing Program (ITP; n = 2635 UM-HET3 mice), across three research sites to assess whether housing density influenced longevity differently in male and female mice. Mice were housed in same-sex cages (median = 3 per cage) without reassignment after cagemate death. We applied Cox frailty models incorporating nested random effects for cage and site, with fixed effects for sex, treatment, and time-varying number of living cagemates to estimate hazard ratios, which allowed us to assess the instantaneous risk of death associated with changes in cagemate number. Results showed a significant main effect of the number of living cagemates on mortality and a significant interaction between sex and cagemate count, indicating sex-specific responses. Female mice exhibited a pronounced increase in mortality rate as cage density declined, suggesting a potential role of social buffering in longevity. These findings emphasize the importance of considering social housing dynamics, particularly for female mice, in both experimental design and animal welfare protocols. Graphical Abstract

Satellite-based spatial-statistical modeling of daily stream water temperatures at the CONUS scale - Daniel Philippus; Claudia R. Corona; Katie Schneider; Ashley Rust; Terri S. Hogue (Journal of Hydrology, 2025)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

P18-17 No Evidence of E-Cigarette Aerosol-Induced Cisplatin Resistance in Head and Neck Cancer Cells: Findings from the Replica International Study Group - G. Carota; R. Emma; K. Partsinevelos; S. Rust; A. Sun; A. Giordano; V. Volarevic; R. Lesmana; H. Goenawan; M.I. Barliana; A. Arsenijevic; N. Kastratovic; et al. (Toxicology Letters, 2025)

The effect of interstimulus interval on sustained attention - Bonnie Humphrey; Daniel B. Stouffer; Averill Moser-Rust; William S. Helton; Randolph C. Grace; Ximena J. Nelson (Behavioural Processes, 2024)

P01-33 Toxicity induced by cigarette smoke and electronic cigarette aerosols - K. Partsinevelos; R. Emma; A. Distefano; G. Carota; S. Rust; R. Pulvirenti; D. Campagna; R. Polosa; M. Caruso; G. Li Volti (Toxicology Letters, 2024)

A machine learning model for estimating the temperature of small rivers using satellite-based spatial data - Daniel Philippus; Anneliese Sytsma; Ashley Rust; Terri S. Hogue (Remote Sensing of Environment, 2024)

Elephant seismicity: Ichnological and rock art perspectives from South Africa - Charles W. Helm; Andrew S. Carr; Hayley C. Cawthra; Jan C. De Vynck; Mark G. Dixon; Andrew Paterson; Renee Rust; Willo Stear; Guy Thesen; Fred Van Berkel; Monique Van Tonder (Proceedings of the Geologists' Association, 2024)

Non-stationary large-scale statistics of precipitation extremes in central Europe - Felix S. Fauer; Henning W. Rust (Stochastic Environmental Research and Risk Assessment, 2023)
Extreme precipitation shows non-stationarity, meaning that its distribution can change with time or other large-scale variables. For a classical frequency-intensity analysis this effect is often neglected. Here, we propose a model including the influence of North Atlantic Oscillation, time, surface temperature and a blocking index. The model features flexibility to use annual maxima as well as seasonal maxima to be fitted in a generalized extreme value setting. To further increase the efficiency of data usage, maxima from different accumulation durations are aggregated so that information for extremes on different time scales can be provided. Our model is trained to individual station data with temporal resolutions ranging from one minute to one day across Germany. Models are chosen with a stepwise BIC model selection and verified with a cross-validated quantile skill index. The verification shows that the new model performs better than a reference model without large-scale information. Also, the new model enables insights into the effect of large-scale variables on extreme precipitation. Results suggest that the probability of extreme precipitation increases with time since 1950 in all seasons. High probabilities of extremes are positively correlated with blocking situations in summer and with temperature in winter. However, they are negatively correlated with blocking situations in winter and temperature in summer.

Implications of fire-induced evapotranspiration shifts for recharge-runoff generation and vegetation conversion in the western United States - Natalie M. Collar; Brian A. Ebel; Samuel Saxe; Ashley J. Rust; Terri S. Hogue (Journal of Hydrology, 2023)

Have farmers had enough of experts? - Niki A. Rust; Petra Stankovics; Rebecca M. Jarvis; Zara Morris-Trainor; Jasper R. de Vries; Julie Ingram; Jane Mills; Jenny A. Glikman; Joy Parkinson; Zoltan Toth; Regina Hansda; Rob McMorran; et al. (Environmental Management, 2022)
The exponential rise of information available means we can now, in theory, access knowledge on almost any question we ask. However, as the amount of unverified information increases, so too does the challenge in deciding which information to trust. Farmers, when learning about agricultural innovations, have historically relied on in-person advice from traditional ‘experts’, such as agricultural advisers, to inform farm management. As more farmers go online for information, it is not clear whether they are now using digital information to corroborate in-person advice from traditional ‘experts’, or if they are foregoing ‘expert’ advice in preference for peer-generated information. To fill this knowledge gap, we sought to understand how farmers in two contrasting European countries (Hungary and the UK) learnt about sustainable soil innovations and who influenced them to innovate. Through interviews with 82 respondents, we found farmers in both countries regularly used online sources to access soil information; some were prompted to change their soil management by farmer social media ‘influencers’. However, online information and interactions were not usually the main factor influencing farmers to change their practices. Farmers placed most trust in other farmers to learn about new soil practices and were less trusting of traditional ‘experts’, particularly agricultural researchers from academic and government institutions, who they believed were not empathetic towards farmers’ needs. We suggest that some farmers may indeed have had enough of traditional ‘experts’, instead relying more on their own peer networks to learn and innovate. We discuss ways to improve trustworthy knowledge exchange between agricultural stakeholders to increase uptake of sustainable soil management practices, while acknowledging the value of peer influence and online interactions for innovation and trust building.

Large silicic magma bodies and very large magnitude explosive eruptions - R. S. J. Sparks; J. D. Blundy; K. V. Cashman; M. Jackson; A. Rust; C. J. N. Wilson (Bulletin of Volcanology, 2022)
Over the last 20 years, new concepts have emerged into understanding the processes that lead to build up to large silicic explosive eruptions based on integration of geophysical, geochemical, petrological, geochronological and dynamical modelling. Silicic melts are generated within magma systems extending throughout the crust by segregation from mushy zones. Segregated melt layers become unstable and can assemble into ephemeral upper crustal magma chambers rapidly prior to eruption. In the next 10 years, we can expect major advances in dynamical models as well as in analytical and geophysical methods, which need to be underpinned in field research.

A new species of tumbling flower beetle (Coleoptera: Mordellidae) from Baltic amber - Tong Bao; Katarzyna S. Walczyńska; Błażej Bojarski; Ed Jarzembowski; Bo Wang; Jes Rust (PalZ, 2019)

How do Europeans want to live in 2040? Citizen visions and their consequences for European land use - Marc J. Metzger; Dave Murray-Rust; Joske Houtkamp; Anne Jensen; Inge La Riviere; James S. Paterson; Marta Pérez-Soba; Christiane Valluri-Nitsch (Regional Environmental Change, 2018)

Experimental phase equilibria of a Mount St. Helens rhyodacite: a framework for interpreting crystallization paths in degassing silicic magmas - Jenny M. Riker; Jonathan D. Blundy; Alison C. Rust; Roman E. Botcharnikov; Madeleine C. S. Humphreys (Contributions to Mineralogy and Petrology, 2015)

MeMoVolc consensual document: a review of cross-disciplinary approaches to characterizing small explosive magmatic eruptions - L. Gurioli; D. Andronico; P. Bachelery; H. Balcone-Boissard; J. Battaglia; G. Boudon; A. Burgisser; M. R. Burton; K. Cashman; S. Cichy; R. Cioni; A. Di Muro; et al. (Bulletin of Volcanology, 2015)

Evolution of crust- and core-dominated lava flows using scaling analysis - Angelo Castruccio; A. C. Rust; R. S. J. Sparks (Bulletin of Volcanology, 2013)

Utilization of Biochar in Sugarcane and Sugar-Industry Management - R. G. Quirk; L. Van Zwieten; S. Kimber; A. Downie; S. Morris; J. Rust (Sugar Tech, 2012)

Movements of hatchery-reared lingcod released on rocky reefs in Puget Sound - Jonathan S. F. Lee; Barry A. Berejikian; Michael B. Rust; Ken Massee; Terry Wright; Kyle Brakensiek; Scott Steltzner; H. Lee Blankenship (Environmental Biology of Fishes, 2011)

Effects of biochar from slow pyrolysis of papermill waste on agronomic performance and soil fertility - L. Van Zwieten; S. Kimber; S. Morris; K. Y. Chan; A. Downie; J. Rust; S. Joseph; A. Cowie (Plant and Soil, 2010)

The effects of thiamine inhibition on ruminal fermentation: a preliminary study - E. M. Ungerfeld; S. R. Rust; R. Burnett (Folia Microbiologica, 2009)

Competition in mixed stands of beech and spruce: effects of climate and ozone - S. Rust; A. Roloff (European Journal of Forest Research, 2009)

Postglacial fault movement and palaeoseismicity in western Scotland: A reappraisal of the Kinloch Hourn fault, Kintail - Iain S. Stewart; Callum R. Firth; Derek J. Rust; Philip E.F. Collins; Judith A. Firth (Journal of Seismology, 2001)

The effect of shoot architecture on hydraulic conductance in beech ( Fagus sylvatica L.) - S. Rust; R. F. Hüttl (Trees, 1999)